Australian recommendations for the management of hepatitis C virus infection: a consensus statement. Issue 7 (18th April 2016) - Thompson, Alexander JV
Summary: Chronic hepatitis C virus (HCV) infection affects 230 000 Australians, who are at risk of progressive liver fibrosis leading to cirrhosis, liver failure and hepatocellular carcinoma. HCV infection is curable, and all Australians living with HCV should be considered for antiviral therapy. Interferon‐free regimens involving combinations of sofosbuvir, ledipasvir, daclatasvir and/or ribavirin for 8, 12 or 24 weeks are now listed on the Pharmaceutical Benefits Scheme (PBS) for treating people with genotypes 1–3 HCV. Treatment for genotypes 4–6 HCV involves sofosbuvir plus peginterferon‐alfa and ribavirin for 12 weeks. The PBS listing allows these therapies to be prescribed by specialists experienced in treating chronic HCV infection or by general practitioners in consultation with one of these specialists. People with cirrhosis and other special populations (eg, those with decompensated liver disease or renal impairment) should be referred for specialist care. Key issues during pre‐treatment assessment include identifying HCV genotype, evaluating for cirrhosis and considering concomitant medications for risk of drug–drug interactions.